The Emergence of the Wagner Group in Mali: An Overview from the Perspective of Conventional Constructivism - Vieri Abdurrafi; Arfin Sudirman; Muhammad Fikry Anshori (Andalas Journal of International Studies (AJIS), 2025)
Wagner Group is a Russian private military company that provides security services in conflict-affected countries. Mali stands out as Wagner Group's key security partners because Wagner entered an already fragmented rebellion, while replacing France as the state’s principal security partner. The interaction of these two actors is a complex dynamic in international relations. Wagner Group, as a non-state actor, signed a security agreement with the Malian government following the military coups of 2020 and 2021. The emergence of the Wagner Group in Mali raises serious concerns about the legitimacy of private military company operations in conflict areas. The purpose of this research is to investigate the reasons or motives for the Wagner Group's presence in Mali by looking at international norms governing private military companies, as well as the Malian state's national identity and interests through the lens of conventional constructivism that emphasises the dialectical relationship between actors and structures. The study employs a qualitative research method with an analytical descriptive approach. Data were gathered through online research, literature reviews, and documentation. To ensure data validity, triangulation techniques were used to increase the reliability and depth of the study. The findings show that Wagner Group operates in the normative grey areas of international law, reconstructing the narrative of the self-defense norm to legitimize security privatization. Furthermore, a shift in Mali's national identity based on anti-colonial perception has allowed political elites to justify the Wagner Group's presence as a means of safeguarding national sovereignty against terrorism and internal instability.